2012
DOI: 10.2337/db11-1503
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 1 Activation Enhances Gut Glucagon-Like Peptide-1 Secretion and Improves Glucose Homeostasis

Abstract: Type 2 diabetes mellitus (T2DM) is rapidly prevailing as a serious global health problem. Current treatments for T2DM may cause side effects, thus highlighting the need for newer and safer therapies. We tested the hypothesis that dietary capsaicin regulates glucose homeostasis through the activation of transient receptor potential vanilloid 1 (TRPV1)-mediated glucagon-like peptide-1 (GLP-1) secretion in the intestinal cells and tissues. Wild-type (WT) and TRPV1 knockout (TRPV1−/−) mice were fed dietary capsaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 50 publications
5
139
2
1
Order By: Relevance
“…5), a result that can be rationalized by cannabinoid receptor activation counteracting the GPR119 agonist-induced rise in cAMP levels. The TRPV1 antagonist SB-366791 lowered both basal and OEA-induced GLP-1 secretion to a similar extent, confirming previous observations on the role of TRPV1 in the regulation of GLP-1 secretion (34). The PPAR ligands tesaglitazar and GW-9662 had no impact on basal or OEA-induced GLP-1 secretion.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…5), a result that can be rationalized by cannabinoid receptor activation counteracting the GPR119 agonist-induced rise in cAMP levels. The TRPV1 antagonist SB-366791 lowered both basal and OEA-induced GLP-1 secretion to a similar extent, confirming previous observations on the role of TRPV1 in the regulation of GLP-1 secretion (34). The PPAR ligands tesaglitazar and GW-9662 had no impact on basal or OEA-induced GLP-1 secretion.…”
Section: Resultssupporting
confidence: 88%
“…Recently, the TRPV1 channel has been implicated in the regulation of GLP-1 secretion, and the TRPV1 agonist capsaicin has been reported to trigger GLP-1 secretion in STC-1 cells (34). In GLUTag cells, we did not see a significant modulation of GLP-1 secretion with arvanil under basal conditions, whereas the selective TRPV1 antagonist SB-366791 inhibited basal GLP-1 secretion.…”
Section: Discussioncontrasting
confidence: 60%
“…38 Our previous studies showed that TRPV1 activation by dietary capsaicin alleviates metabolic disorders and attenuates aortic atherosclerosis as well as hypertension. 21,33,39,40 In this study, we further demonstrated that chronic dietary capsaicin supplementation ameliorated HFDinduced endothelial dysfunction in the coronary arteries and prolonged the lifespan of ApoE −/− receiving HFD. Moreover, we showed that the activation of TRPV1 by dietary capsaicin increased UCP2 expression and reduced ROS generation in ECs and arteries, and that these effects were associated with −/− mice fed with HFD or HC.…”
Section: Trpv1 Activation Antagonizes Ros-mediated Coronary Lesions Bsupporting
confidence: 61%
“…25 After an overnight fast, GTT or ITT were performed by intraperitoneal injection of glucose (2 g/kg) or insulin (0.75 U/kg) in sterile saline, respectively. Blood glucose was measured at 0, 15, 30, 60, 90 and 120 min by an OneTouch Ultra blood glucose meter (OMRON, Kyoto, Japan).…”
Section: Intraperitoneal Glucose Tolerance and Insulin Tolerance Testsmentioning
confidence: 99%